Phosphate adsorption characteristics of soils, slags and zeolite to be used as substrates in constructed wetland systems - Sakadevan, K.; Bavor, H.J. (Water research (Oxford), 1998)
Constructed wetlands are used to remove pollutants from wastewater. The performance of such wetlands to remove pollutants from wastewater can be improved by using suitable substrates. In this study the phosphorus (P) adsorption capacities of soils, two industrial by-products and a clinoptilolite material (zeolite) were examined for their potential use as substrates to remove P in constructed wetlands. Both Freundlich and Langmuir adsorption isotherms were used to describe the adsorption characteristics of these substrates. The Langmuir adsorption isotherm was used to calculate the maximum P adsorption capacity of these substrates. One of the industrial by-products, namely blast furnace slag, showed the highest P adsorption capacity (44.2 g P kg −1 slag) followed by soil samples collected from an operating (Byron Bay) constructed wetland system in Northern NSW (4.2 to 5.2 g P kg −1 soil). The surface soils collected from two regional constructed wetland systems were found to have the least P adsorption capacity (1153 and 934 mg P kg −1 soil, respectively for Richmond and Carcoar wetlands). The clinoptilolite material (zeolite), which is used to remove ammonium ion from wastewater, was found to have a P adsorption capacity of 2.15 g kg −1. The relationship between P adsorption and oxalate extractable iron (Fe) and aluminium (Al) showed that P adsorption related more closely to extractable Al (r 2 = 0.890) than Fe (r 2 = 0.736). Multiple regression analysis showed that P adsorption is more closely related to a combination of both oxalate extractable Fe and Al (r 2 = 0.901) than extractable Fe or Al alone. The P saturation capacity of wetland systems incorporating these substrates is described. The results suggest that selected industrial by-products and adsorptive materials may be used alone or in combination with soils to improve the performance of constructed wetland systems subject to other properties such as pH, permeability and structural stability of these materials.